Correlation of P53 Expression with Histological Grade and Histological Type of Invasive Breast Carcinoma (Journal of Fatima Jinnah Medical University, 2018)
Objective: To evaluate expression of P53 in different types of breast CA and correlate it with different grades of invasive ductal CA. Study design: It is a descriptive study Place and duration of study: Pathology Department, Post Graduate Medical Institute (PGMI) from 2nd January 2014 to 3rd January 2015. Material & Methods: A total of 71 specimens diagnosed with invasive breast carcinoma in all surgical specimens (excisional biopsy, incisional biopsies mastectomies) were included in the study. P53 immunohistochemical staining was applied on all the cases. DAKO FLEX monoclonal mouse anti human P53 protein kit was used. P53 staining was done on 4mm sections and interpreted under the microscope. Typing and grading of carcinoma was done according to WHO classification and P53 expression was observed in different types and grades of breast carcinoma. Statistical package for social sciences 20 Data was used for analysis. Qualitative expression was presented in the form of frequency and percentage. Results: From 71 patients, all 09 cases of grade I carcinoma were P53 negative, 22 cases of grade II carcinoma were P53 negative whereas 12 cases were positive. Among 22 cases of grade III breast carcinoma, 16 were P53 positive while 06 were negative. P53 showed different expression in different types of breast carcinoma. P53 positivity was seen in 28 of 65 cases while rest (37) was negative for it. Mucinous carcinoma showed positivity in 50% of the cases (one was positive and one was negative). Similar results were seen in invasive lobular carcinoma as seening mucinous carcinoma. P53 showed 100% positivity in poorly differentiated (1/1) and metaplastic carcinoma (1/1). Conclusion: P53 positive expression is a poor prognostic marker. It is seen more frequently in carcinoma with poor prognosis and less frequently in carcinomas with better prognosis
Keywords: Invasive breast CA, p53, histological grade, Histological type